Analisa Performansi Mesin Diesel MAK 8M453 Tipe 4 Langkah dengan Daya Terpasang 2500 kW - Yufitriani Littik (Jurnal Penelitian Rumpun Ilmu Teknik, 2022)
In actual diesel engine work cycle is part of the heat input that occurs at constant volume and partly at constant pressure. Therefore, in the calculation of the design of the modern diesel motor cycle, a limited pressure air cycle (combined cycle) is used. The purpose of this study is to analyze the performance of the diesel engine in the PLTD Tenau-Kupang and to find out the deviations or losses that occur in the diesel motor work cycle. From the results of the research in the form of an analysis of calculations at 600 rpm engine speed, it can be concluded that the basic factors of the performance of an engine include the average effective pressure (MEP), piston speed, ratio of stroke length and cylinder diameter, number of cylinders, and calculations for power. The resulting motor is close to the actual motor power.